ITALIAN GRADUATIONS DAY: A NEW MODEL OF RITUAL - Riconda, Giorgia (Journal of Education Culture and Society, 2019)
Aims.The research aims to reconstruct the phases of the new ritual of graduation in Italy to fully understand if there are a variety of social forms and conventions (linked to symbolic aspects) to be satisfied and if there are elements of ambiguity.Methods.Using ethnographic technique, I chose to develop on the one hand a thick description of the ritual that highlights the "stratified hierarchy of significant structures" (Geertz 1998) while on the other I tried to develop a comparative methodology that takes into account - both temporal and spatial level - of some of the different graduation ritual models that exist and have existed.Results.  The analysis shows that there is a lack of consistency between the new degree model and the new graduation ceremony model. Furthermore, in the one hand, the liminal theatricality of the rite satisfies the demands of collective catharsis; on the other hand, there are some ambivalences and there is a lack of consistency between the conventions (and its symbolisms) in the ceremony and the university experiences that students could have in Italy.Lastly, the moral entrepreneurs paid too little attention to the original meanings of the model of celebration from which it draws and its criticality.Conclusions.Rituals in the educational field are very important socio-cultural forms of production of meanings whose modification could be more satisfactory if there was a greater reflection on the original educational models and if, in this reflection, they were involved a large number of subjects belonging to different groups.